Analisis Kerahasiaan Rekam Medis Berdasarkan Hak Akses Ruang Filing Rawat Jalan di RSUD Dr.Saiful Anwar Malang - Eva Tri Wicahyanti; Maya Weka Santi; Rossalina Adi Wijayanti (Politeknik Negeri Jember, 2020)
Confidentiality of medical records at RSUD Dr. Saiful Anwar Malang still had several obstacles in implementation, where there were non-medical record officers who enter and exit the outpatient filing room although there was finger prints and written warnings stating that